‫السنة‬ ‫مفهوم‬ ‫من‬ ‫الليبرالي‬ ‫الاتجاه‬ ‫موقف‬ - Zahrul Fata (TSAQAFAH, 2015)
One of the major issues that has occupied intellectual discourses in the contemporary Muslim World pertains to practicing historicism on Islamic religious texts (al-Qur’an and al-Sunnah). This study seeks to examine and respond to some efforts that have been done by liberal thinkers, Indonesian as well non-Indonesian, to redefine the concept of Sunnah based on historicism, the view that historical awareness is crucial for adequate understanding in a particular fieldor in general. After using both deductive and critical-analytical methods, this study has come to the conclusion that the concept of Sunnah which has been put forward by Indonesian liberal thinkers is mere repetition of contemporary Muslim thinkers, Arab as well non-Arab, who came under spell of the Orientalists. For liberal thinkers, Sunnah is not identical with hadits. According to their view, the conventional conception of Sunnah which means all that was delivered by the Prophet (SAW), whether by word of mouth, deed, prescription, and character (either physical or ethical), has caused the decline of Islam. Thus, in the their opinion, the sound definition of Sunnah that suits the contemporary era involves the prophet’s personal reasoning (ijtihâd) in executing the injunctions of the holy book, namely, penalties (hudûd), worship, and ethics while accounting for the realistic (objective) world wherein he lived. Therefore, based on this view, the Sunnah should not be implemented literally as the Prophet did, but rather it could be changed due to some circumstances. No doubt that such concept needs boundaries, that is to say, which are principles and which are not in Islam. Otherwise, such a view is not only against the universality of Sunnah itself, but also a kind of effort to eliminate the role of Sunnah from Muslim life.